Proses Komunikasi yang Efektivitas Dalam Organisasi - Effendy, Erwan; Agni, Mahisa; Putri, Melinda Rianto; Firdasari, Senang (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The purpose of this article is to find out about how an effective communication process can be carried out in organizations. Because in reality there is communication that will appear in every organizational process. The research method used in this article is qualitative which uses the method of literature study. To create effective communication, a communicator must be able to identify targets who are recipients of messages, determine communication goals, design messages, choose media, choose message sources, and collect messages. feedback. To build effective communication five important foundations are needed, namely the effort to truly understand other people, the ability to fulfill commitments, the ability to explain expectations, the willingness to sincerely apologize if you make a mistake, and the ability to show integrity. Keywords: Communication Process, Effectiveness and Organization